A Comparative Study on Longitudinal Dynamics Stability Between Two Aircraft Models - Pairan, Mohammad Fahmi; Basuno, Bambang; Firdaus, Muhammed Daniel; Shamsudin, Syariful Syafiq (Progress in Aerospace and Aviation Technology, 2022)
The present work presents a comparative study on the longitudinal dynamic’s stability behavior for two aircraft models, namely the Learjet 24 and the Cessna 182. The longitudinal flight dynamics behaviors are evaluated by introducing a disturbance to the elevator. This device uses a single doublet impulse as well as multiple doublet impulses. The governing equation of longitudinal flight motion, which was derived based on a small perturbation theory and a linearized process by dropping the second order and above to the disturbance quantities, allowed one to formulate the governing equation of flight motion in the form of an equation known as the longitudinal equation of flight motion. This equation describes the flight behavior of an aircraft and can be expressed in the disturbance quantity as translational velocity in the x-direction u, angle of attack , and pitch angle . The implementation in the case of the Cessna 182 and the Learjet 24, where the Cessna 182 uses a single doublet impulse or a multiple doublet impulse, demonstrates that the aircraft response in these three variable states is better than that of the Learjet 24.